Unruly Catholic feminists : prose, poetry, and the future of the faith - DelRosso, Jeana; Eicke, Leigh Anna; Kothe, Ana (Excelsior editions., 2021)
Third- and fourth-wave feminists write about their experiences with Catholicism and their visions for the future of women in the Church.